Problem praktyczny biznesu - Stańczyk, Piotr (THE Practical Problem Of Business, 2008)
Summing up, at knowledge offered as business conceptual support, we can look through the prism of rational criteria of practical directives. Directive is the answer to the practical problem, therefore it should take into consideration all parts of the practical problem. Directive is some alpha structure which should be incentives structure causing proper actions in the same time. That condition can be complied if in the structure of practical problem, the dimension (aspect) of the fundamental description is taken into consideration.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 122-138